1000 successful Kielland deliveries. (18th April 2012) - Tempest, N; Hart, A; Walkinshaw, S; Hapangama, D
Abstract : Background: The rates of caesarean sections are increasing globally and malposition of the fetal head is a common reason for emergency caesarean section during the second stage of labour. There are no recent or large studies concentrating on mode of delivery when rotation is necessary. Aims: To compare the outcomes of Kielland forcep deliveries with other methods of delivery for malposition of the fetal head in the 2 nd stage of labour in a tertiary hospital. Methods: Retrospective review of outcomes of all consecutive kielland forceps (KF) deliveries over a 50 month period with reference to all rotational ventouse (VEN) and all caesarean sections in the second stage of labour for malposition (EMCS). Results: The outcomes of 1291 malposition deliveries were analysed. KF were successful in 96.3% of attempts vs 77.6% of VEN. KF deliveries had a rate of adverse maternal and neonatal outcomes comparable to VEN and EMCS. The incidence of Massive obstetric haemorrhage in KF vs VEN vs EMCS was 1.8% vs 1.9% vs 2.1%. Admission to SCBU in KF 10.3%, 12.1% in VEN and 11% in EMCS. Conclusions: The use of Kielland's forceps is associated with an increased number of successful vaginal deliveries, without a significant increase in adverse outcome for mothers or babies. Training in assisted delivery by all methods of rotational vaginal delivery, including Kielland's forceps, is of the upmost importance to influence the ever rising rate of caesarean sections in order to provide best outcomes for mothers and babies.